Status of Immediate Versus Delayed Loading of Dental Implants in a Tertiary Care Teaching Hospital - Chakraborty, Somnath (Asian Journal of Medical Research, 2020)
Background: A proven solution for rehabilitation of partial or entire edentulism is dental implants and the survival charge of implant supported restrorations is relatively high. Due to this fact an increasing number of human beings are choosing dental implants for rehabilitation. For single tooth gaps, implants serve as a treasured replacement alternative as proven by way of huge quantity of studies. Subjects and Methods: Total of forty six (46) patients reporting for the replacement of single missing tooth. Patients between age of 19-53 years have been enrolled within the study. Results: The mean bone levels on mesial and distal side amongst Group 1 subjects at 6 months were 0.74 0.24 and 0.66 0.23 respectively. The mean bone levels on mesial and distal side amongst Group 1 subjects at 12 months were 1.12 0.33 and 1.03 0.34 respectively. The mean bone levels on mesial and distal side amongst Group 2 subjects at 6 months were 0.77 0.19 and 0.71 0.52 respectively. The mean bone levels on mesial and distal side amongst Group 2 subjects at 12 months were 1.15 0.14 and 1.13 0.32 respectively. Conclusion: Comparison instant and not on time loading of the implants. Immediate loading established a surprisingly successful scientific outcome at the end of one year. But the survival rate of the implant that have been loaded immediately turned into inferior to those loaded by using conventional approach.